Management of Student Pick-Up and Drop-Off Service In Islamic Educational Institutions - Romdonah, Nonah; Sopwandin, Iwan; Patmawati, Ai Dini (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2026)
The different conditions of rural environments cause access to educational institutions to be diverse, not infrequently this is the reason students are late to school, furthermore many students do not want to continue school because of the very long distance. Therefore, educational institutions' provision of pick-up and drop-off services represents a viable solution for students. This study aims to analyze the management of pick-up and drop-off services at Madrasah Ibtidaiyah Attaufiq Bojongasih Tasikmalaya. The method used in this study is qualitative with a descriptive analysis approach with data collection techniques through observation, semi-structured interviews and documentation studies. The data analysis technique is carried out with an interactive model that includes data condensation, data presentation and conclusion drawing. The results of the study show that: 1) The management of pick-up and drop-off services at Madrasah Ibtidaiyah Attaufiq Bojongasih Tasikmalaya is carried out through planning that begins with problem identification, organizing, implementing, and evaluating; 2) The implementation of pick-up and drop-off services at the Attaufiq Bojongasih Tasikmalaya Elementary Madrasah is supported by several factors, including the commitment of the madrasah principal, support from teachers, participation from parents, and a culture of mutual cooperation within in the community.